GERAKAN TAMAN BACA “PERPUSTAKAAN DUSUN” DARIMAHASISWA UNTUK DESA - Arif Wibowo (Asian Journal of Innovation and Entrepreneurship, 2013)
Books and reading are two sides of the coin are interrelated. Although it's beena variety of media to facilitate reading but still bukulah which is the main choice.Familiarize read takes the process and time to be membumikannya in everyday life.Environmental factors and the lack of facilities greatly affect it. That's what happened inthe hamlet villagecommunities Wonosaran. For the manufacture of garden reading amidthe village into one solution that can be done to improve and facilitate the publicinterest, especially children. Providing books by utilizing the donation and procurementof other supporting facilities involving the community in these activities as well as aseparate education in this program. With the expected realization of the village libraryliteracy read on society can be realized. Aside from the manufacture of the villagelibrary isa manifestation of concern to the community andeducation of students.